Autogenous Formation of Gold on Layered Black Phosphorus for Catalytic Purification of Waste Water - Veselý, Martin; Marvan, Petr; Trejbal, Jiří; Mazánek, Vlastimil; Luxa, Jan; Šturala, Jiří; Sofer, Zdeněk (ACS applied materials & interfaces, 2020)
Layered black phosphorus (BP) is a member of a layered material family with anisotropic properties and layer-dependent band gaps that can be exfoliated down to single-layered phosphorene. Compared with graphene, few-layered BP and its single-layer phosphorene are significantly more reactive, and this reactivity can be applied for the autogenous reduction of gold ions to metallic gold nanoparticles supported by few-layered BP (Au/BP). Few-layered BP and gold are well-known oxidation catalysts important in organic synthesis and also in the catalytic treatment and purification of industrial wastewater. The treatment of organic contamination present in industrial wastewater presents serious problems and is an important issue for current catalysis. Here, we show the high catalytic activity of the gold supported on few-layered black phosphorus (Au/BP) for wet oxidation of acrylic acid, including samples of industrial wastewater with complex composition. The catalyst Au/BP exhibits high stability, which allows utilization of its easily accessible 2D surface for the preparation of 2D material-supported metal catalysts.